E-commerce sector in the circular economy development – hazards and prospects - Lorek, Paweł (Sektor e-commerce w rozwoju gospodarki okrężnej – zagrożenia i perspektywy, 2021)
This article touches upon the issue of the interaction between the specificity of the e-commerce industry and the principles of the circular economy. The circular economy is currently the preferred economic model in the European Union, which covers all market participants, i.e. producers, distributors and consumers. At the same time, a strong increase in the popularity of e-commerce platforms has been recorded among consumers. This situation warrants taking up an analysis of the contact points between the circular economy and e-commerce concepts. The purpose of the article was to analyse the opportunities and threats related to the functioning of e-commerce platforms in the conditions of transformation towards a green economic order and circular economy. A desk study was applied as research methods with the use of literature on the subject and SWOT analysis. The result of the analyses is a systematized form of opportunities and threats related to the functioning of e-commerce platforms in a circular economy.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 3 (61), s. 24-31
Keywords: e-commerce; circular economy; SWOT analysis; internet technologies; gospodarka okrężna; analiza SWOT; technologie internetowe